Fed-Batch mcl- Polyhydroxyalkanoates Production in Pseudomonas putida KT2440 and ΔphaZ Mutant on Biodiesel-Derived Crude Glycerol - Borrero-de Acuña, José Manuel; Rohde, Manfred; Saldias, Cesar; Poblete-Castro, Ignacio (Frontiers in Bioengineering and Biotechnology, 2021)
Crude glycerol is a suitable feedstock for the biotechnological production of industrial chemicals given its high surplus catalyzed by the biodiesel industry. Pseudomonas bacteria metabolize it into several biopolymers, including alginate and medium-chain-length poly(3-hydroxyalkanoates). Although P. putida is capable of deriving these polyoxoesters from crude glycerol, concentrations in batch and fed-batch cultures are still low. Here, we employed P. putida KT2440 and the ΔphaZ-mutant in two different fed-batch modes to synthesize mcl-PHAs from raw glycerol. Initially, the cells grew in a batch phase (µmax 0.21 h-1) for 22 h followed by a carbon-limiting exponential feeding, being the specific growth rate 0.1 (h-1), resulting in a cell dry weight (CDW) of nearly 50 (g L-1) after 40 h. During the PHA production stage, we supplied the substrate at a constant rate of 50 (g h-1), where the KT2440 and the ΔphaZ produced 9.7 and 12.7 gPHA L-1, respectively, after 60 h. We next evaluated the P. putida strains PHA production using a DO-stat approach under nitrogen depletion. Citrate was the main byproduct secreted, accumulating up to 48 (g L-1). The mutant ΔphaZ amassed 38,9% of the CDW as mcl-PHA and exhibited a specific PHA volumetric productivity of 0.34 (g L-1 h-1), 48% higher than the wild-type. The biosynthesized mcl-PHAs had average molecular weights ranging from 460 to 505 (KDa) and a polydispersity index (PDI) of 2.4-2.6. Here, we demonstrated that the DO-stat feeding approach in high-cell-density cultures yields superior production of mcl-PHA in P. putida strains using the industrial crude glycerol.